2017
DOI: 10.2174/1570159x15666161111113514
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacogenetics and Pharmacotherapy of Military Personnel Suffering from Post-traumatic Stress Disorder

Abstract: Background:Posttraumatic stress disorder (PTSD) is a severe problem among soldiers with combating experience difficult to treat. The pathogenesis is still not fully understood at the psychological level. Therefore, genetic research became a focus of interest. The identification of single nucleotide polymorphisms (SNPs) may help to predict, which persons are at high risk to develop PTSD as a starting point to develop novel targeted drugs for treatment.Methods:We conducted a systematic review on SNPs in genes re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 173 publications
(178 reference statements)
0
4
0
1
Order By: Relevance
“…VMAT2 acts in all monoaminergic brain regions, and thus variation in its expression has wide‐ranging effects on neurochemical transmission . It is difficult to attribute any one of the behavioral phenotypes described in this study to a particular monoamine neurotransmitter system or brain region; indeed, genetic variation in multiple monoaminergic systems, including in monoaminergic vesicular packaging itself, has been implicated in risk for PTSD . All three major central monoamine systems (dopamine, norepinephrine and serotonin) interact with each other, and individually to contribute to PTSD outcomes.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…VMAT2 acts in all monoaminergic brain regions, and thus variation in its expression has wide‐ranging effects on neurochemical transmission . It is difficult to attribute any one of the behavioral phenotypes described in this study to a particular monoamine neurotransmitter system or brain region; indeed, genetic variation in multiple monoaminergic systems, including in monoaminergic vesicular packaging itself, has been implicated in risk for PTSD . All three major central monoamine systems (dopamine, norepinephrine and serotonin) interact with each other, and individually to contribute to PTSD outcomes.…”
Section: Discussionmentioning
confidence: 91%
“…One avenue of research is to examine the genetic differences between trauma‐exposed individuals who develop PTSD and those that do not . Transgenerational and twin studies indicate that genetics, particularly variation in monoamine systems, play a role in the etiology of PTSD . In a recent candidate gene analysis of more than 3000 single nucleotide polymorphisms across more than 300 genes, the gene SLC18A2 , which encodes the vesicular monoamine transporter 2 (VMAT2), was identified as a risk haplotype for PTSD diagnosis in a cohort of 2538 European women and replicated in an independent cohort of 748 male and female African Americans .…”
Section: Introductionmentioning
confidence: 99%
“…Numerous pharmacological and nutraceutical compounds have been tested in an attempt to alleviate the symptoms of PTSD [18]. One such medication that has shown promise in clinical applications is pregabalin.…”
Section: Introductionmentioning
confidence: 99%
“…GWAS studies showed that ADCY8 polymorphism was associated with various neuropsychiatric disorders, including dissociative amnesia, post-traumatic stress disorder, depression and bipolar disorder [ 37 , 112 , 113 ].…”
Section: Expression and Functions Of Adcys In The Cnsmentioning
confidence: 99%